2021
DOI: 10.1177/00957984211034948
|View full text |Cite
|
Sign up to set email alerts
|

Black Psychology and Whiteness: Toward a Conceptual Model of Black Trauma through the Prism of Whiteness

Abstract: The main objective of this article is to introduce and examine whiteness as a source of trauma for Black people. We explore Black psychology scholarship to conceptually ground whiteness as the impetus for racism, while identifying it as an interpersonal, psychosocial, and contextual phenomenon that informs the race-based traumatic experiences of Black people. The primary factors constituting whiteness are ethnocentric monoculturalism, White standardization, ontological expansiveness, White emotions, attitudes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 86 publications
(154 reference statements)
0
8
0
Order By: Relevance
“…Similarly, race‐based trauma fails to account for the many identities Black women carry by inserting a race‐only analysis of trauma. Literature on race‐based trauma focuses on Black men only (Aymer, 2016; Lipscomb et al., 2019), does not include a substantive analysis of gender‐based trauma (Hargons, 2021), or couples the experiences of Black women with those of white women (Tyler et al., 2021).…”
Section: Relevant Literaturementioning
confidence: 99%
“…Similarly, race‐based trauma fails to account for the many identities Black women carry by inserting a race‐only analysis of trauma. Literature on race‐based trauma focuses on Black men only (Aymer, 2016; Lipscomb et al., 2019), does not include a substantive analysis of gender‐based trauma (Hargons, 2021), or couples the experiences of Black women with those of white women (Tyler et al., 2021).…”
Section: Relevant Literaturementioning
confidence: 99%
“…If psychologists continue to allow whiteness to flourish in our discipline without interrogating it, we are complicit with a psychology that embraces White ways of knowing, theorizing, evaluating, and teaching. While whiteness studies are growing, the construct has not received significant attention by psychologists until recently (Coleman et al, 2021;Collins & Watson, 2021;Ferguson et al, 2022;Fine al., 2004;Karras et al, 2021;Remedios, 2022;Salter & Adams, 2013;Teo, 2022;Tyler et al, 2022).…”
Section: Naming Whitenessmentioning
confidence: 99%
“…This is a significant component to improve population sciences and epidemiological approaches used to combat communicable and non-communicable diseases. Various Black scholars, including anthropologists, psychiatrists, and of course psychologists, have explored and introduced culturally informed psychological theory ( Tyler et al, 2022 ). Research in anthropology has shown that whiteness directly reflects into racism, facilitating and fuelling Black trauma ( Drake, 1980 ; Tyler et al, 2022 ).…”
Section: Racism Within Medicine and Psychiatrymentioning
confidence: 99%
“…Various Black scholars, including anthropologists, psychiatrists, and of course psychologists, have explored and introduced culturally informed psychological theory ( Tyler et al, 2022 ). Research in anthropology has shown that whiteness directly reflects into racism, facilitating and fuelling Black trauma ( Drake, 1980 ; Tyler et al, 2022 ). Black Psychology has enabled the advancement of these theories, understanding the experiences and exposures of individuals of Black heritage ( Drake, 1980 ; Tyler et al, 2022 ).…”
Section: Racism Within Medicine and Psychiatrymentioning
confidence: 99%